Utilization of Discovery Learning Model as an Effort to Increase Student Creativity in Islamic Religious Education Learning - Nurdin, Realita; Masram (MADINA : Journal of Islamic Studies, 2024)
This study aims to determine the effectiveness of the application of the discovery learning model in improving students' learning creativity on the material of respect and obedience to both parents. This study uses a qualitative method with a descriptive approach. The sample of the study was 9 students of class XI of At-Ta'lim Retok Majau Private Madrasah Aliyah. This study was conducted in two cycles, each cycle consisting of four stages. The results of the study indicate that the application of the discovery learning model can improve students' learning creativity. This can be seen from the increase in students' creativity in critical thinking, solving problems, and producing work. In the first cycle, the average score of students' learning creativity was 78.38 (fair category). In the second cycle, the average score of students' learning creativity increased to 86.66 (good category). Based on the results of this study, it can be concluded that the application of the discovery learning model is an effective strategy to improve students' learning creativity.